THE INFLUENCE OF SPIRITUAL INTELLIGENCE,LEADERSHIP, AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR: A STUDY TO ISLAMIC BANK IN MAKASSAR CITY - HM, Muhdar.; Rahma, St. (Al-Ulum, 2015)
The aims of this study are to find out and to analys: (1) the influence of spiritual intelligence on organizational  citizenship  behavior; (2) the influence of leadership on organizational  citizenship  behavior; (3) the influence of organizationan culture on organizational  citizenship  behaviorThe population included all employees of Islamic Bank in Makassar City. There were 178 samples determined by using Slovin formula.  The samples were selected in two stages: proportional and purposive sampling. The data were analyzed by using path analysis with the AMOS 21 program. The results show that: spiritual intelligence has a positive and significant influence on organizational citizenship behavior; leadership has a positive and significant influence on organizational citizenship behavior; organizational culture has a positive and significant influence on organizational citizenship behavior.-----Penelitian ini bertujuan untuk mengetahui dan menganalisis: (1) pengaruhkecerdasan spiritual terhadap organizational citizenship behavior, (2) pengaruh kepemimpinan terhadap organizational  citizenship  behavior, (3) pengaruh budaya organisasi terhadap organizational  citizenship  behavior. Penelitianini bersifat deskriptif.   Populasi penelitian adalah seluruh karyawan Bank Umum Syariah di Kota Makassar. Sampel yang  diambil sebanyak 178 orang  dengan menggunakan rumus Slovin.Pengambilan sampel dilakukan melalui dua tahap yaitu sampel  proportional  dan sampel purposif. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi.  Data dianalisis dengan teknik analisis jalur melalui program AMOS 2 .Hasil penelitian menunjukkan bahwa kecerdasan spiritual berpengaruh positif dan signifikan terhadap  organizational  citizenship  behavior,  kepemimpinan berpengaruh positif dan signifikan terhadap organizational  citizenship  behavior, budaya organisasi berpengaruh positif dan signifikan terhadap organizational  citizenship  behavior